The identity of Paradiopatra bihanica (Annelida: Onuphidae) and reinstatement of P. calliopae - Paxton, Hannelore; Arias, Andrés (Zootaxa, 2016)
Examination of the holotype of Paradiopatra bihanica (Intes & LeLoeuff, 1975) indicated that the identity of this species had been incorrectly represented in recent papers and that the ensuing synonymisation of P. calliopae Arvanitidis & Koukouras, 1997 was unwarranted. This led us to researching the history of the holotype and its representation in the literature to reinstate P. calliopae as the correct name for this very common Mediterranean and eastern North Atlantic species (Martínez & Adarraga 2001; Arias & Paxton 2015; Santelli et al. 2015).